2007
DOI: 10.1126/science.1142819
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of an Ancient Protein: Evolution by Conformational Epistasis

Abstract: The structural mechanisms by which proteins have evolved new functions are known only indirectly. We report x-ray crystal structures of a resurrected ancestral protein-the approximately 450 million-year-old precursor of vertebrate glucocorticoid (GR) and mineralocorticoid (MR) receptors. Using structural, phylogenetic, and functional analysis, we identify the specific set of historical mutations that recapitulate the evolution of GR's hormone specificity from an MR-like ancestor. These substitutions reposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
435
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 391 publications
(456 citation statements)
references
References 32 publications
11
435
0
4
Order By: Relevance
“…For the same given set of mutations, it may be that one temporal order of mutations is evolutionarily favoured because it entails a monotonic increase in fitness, whereas another order of mutations is disfavoured because it involves an intermediate step that decreases fitness. Several studies have demonstrated this type of epistatic behaviour in proteins and its constraints on evolutionary pathways [42,53,300,[395][396][397][398]. For instance, experiments on adenylate kinase indicate that a double mutant with higher stability can only be obtained via one mutation path [300].…”
Section: Epistasis and Co-evolution Of Interacting Amino Acid Residuesmentioning
confidence: 99%
“…For the same given set of mutations, it may be that one temporal order of mutations is evolutionarily favoured because it entails a monotonic increase in fitness, whereas another order of mutations is disfavoured because it involves an intermediate step that decreases fitness. Several studies have demonstrated this type of epistatic behaviour in proteins and its constraints on evolutionary pathways [42,53,300,[395][396][397][398]. For instance, experiments on adenylate kinase indicate that a double mutant with higher stability can only be obtained via one mutation path [300].…”
Section: Epistasis and Co-evolution Of Interacting Amino Acid Residuesmentioning
confidence: 99%
“…In this case, enhancement of nGRE-binding ability in the GR lineage and the loss of nGRE-binding ability in the MR and AncSR3 lineages were critical for development of divergent DNA specificity. Both computational and directed evolution studies have implicated epistasis as a primary factor in molecular evolution (34,35), and studies of historical protein divergence have established a major role for epistasis in specific cases (28,(36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…A mutation that is beneficial at the time of its introduction may confer its beneficial effect only in the presence of other potentiating or permissive mutations (1)(2)(3)(4)(5)(6)(7)(8)(9). Thus, the fate of a mutation arising in a population may be contingent on previous mutations (10)(11)(12)(13).…”
mentioning
confidence: 99%